Diseño, fabricación y prueba de una antena de parche para GPS en aplicaciones automotrices - Tecpoyotl-Torres, M.; Vera-Dimas, J. G.; Varona, J.; Escobedo-Alatorre, J.; Koshevaya, S. V; Sánchez-Mondragon, J. (Acta Universitaria, 2011)
This work is focused on the development of a prototype patch antenna designed for use asa replacement antenna in automotive Global Positioning Systems (GPS). In simulations andtesting of the prototype, the focus was on the antenna gain. Transmission-reception testingwas done to verify the operation frequency. The prototype was tested with a commercial GPSkit to evaluate its performance as a replacement antenna. Laboratory testing showed that itcomplied with the minimum requirements for both reception and transmission frequencies,while testing on a stationary vehicle showed slight variations when compared to the positiondata obtained using the same kit with its original antenna. In non-stationary testing, positiondeterminations made with the prototype were sufficiently precise for use.